Light response of gametophyte in Adiantum flabellulatum: transcriptome analysis and identification of key genes and pathways - Cai, Zeping; Wang, Xiaochen; Xie, Zhenyu; Wen, Zhenyi; Yu, Xudong; Xu, Shitao; Su, Xinyu; Luo, Jiajia (Frontiers in Plant Science, 2023)
We are submitting a manuscript titled "Light Response of Gametophyte in Adiantum flabellulatum: Transcriptome Analysis and Identification of Key Genes and Pathways" for your consideration of publication in Frontiers in Plant Science. The text includes 5209 words, 10 figures, 12 supplementary figures, and 24 supplementary tables.i) Highly Sensitive Light Response in Adiantum flabellulatum Gametophytes: The study found that the gametophytes of A. flabellulatum are highly sensitive to light, with significant changes in growth under different photosynthetic photon flux density (PPFD) levels. The optimal PPFD for gametophyte growth was determined to be 7.1 μmol m -2 s -1 , while 145.3 μmol m -2 s -1 induced light stress on the gametophytes.ii) Identification of Differentially Expressed Genes (DEGs) and Pathways: Transcriptome sequencing and analysis identified 10,995 DEGs in A. flabellulatum gametophytes under different PPFD levels. Among these DEGs, key genes related to light signaling, photosynthesis, and photoprotection were identified. For example, down-regulation of PHYBs and CRY1s was observed at low PPFD (0.1 μmol m -2 s -1 ), and DEGs related to photosynthesis and flavonoid biosynthesis pathways were annotated.iii) Transcription Factors and Regulatory Relationships: The study predicted 34 transcription factor families and found a correlation between mTERFs and photosynthesis, as well as a coexpression relationship between MYBs and bHLHs with genes encoding flavonoid synthesis enzymes. This suggests potential regulatory roles of these transcription factors in the light response of A. flabellulatum gametophytes.Overall, this study provides insights into the light response mechanism of fern gametophytes and highlights the importance of light signaling, photosynthesis, and photoprotection pathways in their adaptation to different light conditions. The identification of key genes and regulatory relationships enhances our understanding of the molecular mechanisms underlying the light response in fern gametophytes.We believe that the quality and significance of the manuscript meet the requirements of Frontiers in Plant Science. Your consideration of publishing this manuscript in Frontiers in Plant Science is greatly appreciated.